Stem anatomical studies of some species of Indigofera L. (Leguminosae-Papilionoideae) - C.U, Nwachukwu; H.O, Edeoga; C.Iand, Kemka-Evans; C.J, Iwuanyanwu (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
Stem anatomical studies of eight species of the genus Indigofera species common in Eastern Nigeria was carried out with the aid of a light microscope. This is with a view of establishing taxonomic relationship among the species. The type of epidermal and hypodermal layers, nature and size of corticular vessels and vascular bundle arrangement are some of the characters assessed and discussed among the Indigofera species studied. The 3-5 lignified hypodermal layers found in I. paniculata, I. pulchra and I. tinctoria distinguish these species from the other species of Indigofera studied. Similarly the conjoint collateral and open vascular bundle type present in I. paniculata, I. senegalensis and I.stenophylla are remarkable and diagnostic for taxonomic characterization of these species. The cortex is distinct with the variations in size and number of vessels with bigger vessels occurring at the hypodermal region and gradually reducing in size towards the center as observed in I. paniculata and I. pulchra and possess cells that are closely packed with little or no intercellular spaces. The nature of the endodermal layer shows that it is sclerenchymatous in I. paniculata, I. prieureana and I. pulchra. The presence of tannins and other ergastic substance in the stem of these species further confirms the highly tanninferous nature of these plants and hence their economic values to man. The biosystematic implications of these findings have been discussed in the light of current literature.